Políticas actuales del gobierno ecuatoriano para combatir la trata de niños, niñas y adolescentes; y la reinserción social de los mismos - Jara Urdánigo, Jenifert Estefanía (2015)
The investigation is entitled "Current policies of Ecuadorian government to fight children and adolescents traffic and their reintegration into society." The victims of this crime suffer severe consequences of physical, psychological or sexual abuse whereas they are captured. The development of this research is divided into six chapters, first; "The Problem" this is the approach of it to conclude with the formulation thereof. In order to develop more effective research process will be plating the objectives of both general and specific, continuing with the justification and importance of the content and the limitations founded during the process. Chapter II "Theoretical Framework", it shows the academic research done by others authors in order to give proper development to the investigation, which study the doctrines; it is a review of literature. After, Chapter III studies National and International legislation about Trafficking Persons. In the Chapter IV develops the phenomenon of Trafficking Children and Teenagers. The Chapter V is about public politic to attack Trafficking NNA and finally, on the Chapter VI has the conclusion and recommendations as a result of the investigation…